IMPACT OF SELF-INITIATIVE TO BOOST POSITIVE PRODUCTIVITY IN PURCHASING DEPARTMENT AT HOTEL THE RINRA MAKASSAR - Jessica Miranda Putri; Patak, Andi Anto; La Sunra (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2023)
This study aims to find out how is the self-initiative of employees at purchasing department of Hotel The Rinra Makassar and also to find out how is the positive productivity of employees at Hotel The Rinra Makassar. This research uses the qualitative descriptive method. Data collection techniques use an observation checklist, interview guide, and documentation. The subjects were three employees and one manager at Purchasing Department of Hotel The Rinra Makassar. The data analysis used in this study is data processing which includes the process of collecting and classifying data with the aim of finding useful information as a basis for decision-making Data analysis is an-effort to search and organize notes from observations systematically, and interviews to improve researchers’ understanding of cases studied.